Online learning: A flexible way to learn - Michael, Rene (Cambridge Publishing, 2004)
Perioperative nurses work in an environment of contunual rapid advances in health care and related technology. To provide the necessary care to patients undergoing anaesthesia and surgery, perioperative nurses need specialised knowledge and skills. One way to provide this education is in the form of postgraduate studies. However, accessing this education can be problematic due to workplace obstacles. Consequently, perioperative nurses seeking postgraduate education require a flexible learning environment, such as that provided by online education. The purpose of this paper is to provide a brief discussion on distance education offered through online learning and to give insight into how this approach can meet the educational needs of perioperative nurses.